(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
In this article, the concepts of blockchain technology and smart contracts are considered. The advantages of using blockchain for "smart contracts" are discussed in detail. Contracts are written in the form of code, and then entered into a system managed on the basis of "blockchain", which is designed to monitor their implementation.